Does the Russell Viper Venom time test provide a rapid estimation of the intensity of oral anticoagulation? A cohort study. Issue 5 (May 2015) - Douxfils, Jonathan; Chatelain, Bernard; Hjemdahl, Paul; Devalet, Bérangère; Sennesael, Anne-Laure; Wallemacq, Pierre; Rönquist-Nii, Yuko; Pohanka, Anton; Dogné, Jean-Michel; Mullier, François
Abstract Background Dilute Russell Viper Venom Time (DRVV-T) might be useful in urgent settings for screening patients on Non-VKA Oral Anticoagulants (NOACs). Aim To compare the accuracy of DRVV-T with gold standard assays for the assessment of pharmacodynamics of dabigatran, rivaroxaban and vitamin K antagonist (VKA) in plasma samples from patients. Methods Sixty rivaroxaban, 48 dabigatran and 50 VKA samples from patients were included. DRVV-T was performed in all groups using STA®-Staclot®DRVV-Screen and -Confirm. For NOACs, PT and aPTT were performed using different reagents while plasma drug concentrations were measured by liquid mass-spectrometry (LC-MS/MS). For VKA, INR was performed using RecombiPlasTin 2G®. Results For NOACs, correlations between calibrated STA®-Staclot®DRVV-Confirm and LC-MS/MS (rs = 0.88 and 0.97 for rivaroxaban and dabigatran, respectively) were higher than the ones obtained with STA®-Staclot®DRVV-Screen (rs = 0.87 and 0.91), PT (rs = 0.83 to 0.86) or aPTT (rs = 0.84 to 0.89). Bland Altman analyses showed that calibrated DRVV-T methods tend to overestimate plasma concentrations of NOACs. ROC curves revealed that cut-off to exclude supra-therapeutic levels at Ctrough (i.e. 200 ng/mL) are different for dabigatran and rivaroxaban. Neither STA®-Staclot®DRVV-Screen nor –Confirm correlated sufficiently with the intensity of VKA therapy (rs = 0.35 and 0.52). Conclusions STA®-Staclot®DRVV-Confirm provides a rapid estimation of the intensity of anticoagulation with rivaroxaban or dabigatran without specific calibrators. At Ctrough, thresholds for rivaroxaban and dabigatran can be used to identify supra-therapeutic plasma level. However, this test cannot differentiate the nature of the NOACs. The development of a point-of-care device optimising this method would be of particular interest in emergency situations.